Clinical phenotypes of cow’s milk food allergy in children depending on the molecular profile of sensitization - N. G. Prihodchenko; T. A. Shumatova; E. Yu. Katenkova; D. V. Kovalenko (Аллергология и Иммунология в Педиатрии, 2023)
Introduction. Sensitization to cow’s milk (CM) is one of the most common causes of food allergy (FA) in young children; its clinical manifestations in children are varied, since many organs and systems can be involved in the pathological process.   The purpose: to study the profile of IgE sensitization to the molecular components of CM in children, depending on the clinical phenotype of the disease.   Materials and Methods. Clinical and laboratory examination of 148 children from birth to 12 months with IgE-mediated FA to CM was carried out. The study of sIgE to cow’s milk, nBos d 8, nBos d 4, nBos d 5, nBos d 6 was carried out by the Immuno CAP method. Statistical processing was performed using the Statistica for Windows v. 10.0, StatSoft Inc. (USA).   Results: The conducted clinical and laboratory analysis allowed us to identify the skin (33.3 %; 49/148), gastrointestinal (23.5 %; 35/148) and mixed (43.2 %; 64/148) phenotype of CMA in children. In the structure of clinical phenotypes, the frequency of the mixed phenotype prevailed over the skin (χ2 = 20.51, p < 0.00001) and gastrointestinal phenotype (χ2 = 27.84, p < 0.00001). Sensitization to nBos d 4 has the greatest influence on the formation of the gastrointestinal phenotype (χ2 = 18.67, p = 0.0001). In the formation of skin manifestations, combined sensitization to nBos d 8 + nBos d 6 (χ2 = 14.96, p = 0.0003), nBos d 8 + nBos d 5 (χ2 = 28.44, p < 0.00001) was more common.   Conclusion. The results of the study showed the importance of cow’s milk components in the formation of the clinical phenotype of the disease and can be used to personalize the diagnosis and therapeutic strategy.